Pengaruh Latihan Motorik Berbasis Virtual Reality Terhadap Aktivitas Serum Brain-Derived Neurotrophic Factor (BDNF) Pada Pasien Dengan Kondisi Stroke - Mariel Daba; Nathasya Ferdyastari; Luh Ade Lela (Poltekkes Kemenkes Maluku, 2025)
Stroke remains a leading cause of disability worldwide, and rehabilitation strategies that enhance neuroplasticity are essential for functional recovery. VR has emerged as an innovative approach to motor control training, providing multisensory stimulation and increasing patient engagement. This study aimed to evaluate the effect of VR-based motor control training on serum BDNF levels and upper extremity motor function in stroke patients. A quasi-experimental two-group pretest–posttest design was conducted with 30 stroke patients recruited through purposive sampling, divided equally into VR and control groups. The VR intervention, delivered using Oculus Quest 2, consisted of four sessions (10–20 minutes/session, 2–3 times per week) incorporating modules for bilateral coordination, reaching, gripping, balance, and cognitive–motor dual tasks. Motor function was assessed using the WMFT, and serum BDNF levels were measured pre- and post-intervention using ELISA. Results showed that BDNF levels in the control group remained unchanged (1.24 ng/mL), while the VR group demonstrated a significant increase from 1.45 to 1.54 ng/mL (p < 0.0001). WMFT scores improved in both groups, but the improvement was greater in the VR group (38 ± 0.39 to 42 ± 0.39; p < 0.0001). These findings indicate that VR-based motor training effectively enhances serum BDNF levels and motor function in stroke patients. Further studies with larger samples, more intensive interventions, and long-term follow-up are recommended. Keywords: Virtual Reality, BDNF, Neuroplastisitas, Motor Function, Stroke